Noun imageability facilitates the acquisition of plurals: survival analysis of plural emergence in children - Smolík, Filip (Journal of psycholinguistic research, 2014)
Some research in child language suggests that semantically general verbs appear in grammatical structures earlier than semantically complex, specific ones. The present study examines whether this was the case in nouns, using imageability as a proxy measure of semantic generality. Longitudinal corpus data from 12 children from the Manchester corpus in CHILDES were used to obtain information on the first occurrence of plurals. A total of 3,560 uninflected nouns were identified in the corpora, of which 1,202 were observed in the plural. Survival analyses indicated that the chance of observing a plural form increases with the imageability rating of the noun, even after accounting for the age of acquisition of the uninflected noun, maternal input frequency, and word length. Noun imageability thus facilitates the acquisition of plural forms. This finding contradicts the observations from verbs, and indicates that the acquisition of grammar is facilitated by high imageability rather than semantic generality.
Keywords: Child Language; Language Development; Humans; psycholingvistika; lidé; Female; mužské pohlaví; Infant; Psycholinguistics; Male; předškolní dítě; Vocabulary; kojenec; Child, Preschool; dětská řeč; ženské pohlaví; vývoj řeči; slovní zásoba